The role of safety and security in the suburban railway traffic in the urban agglomerations of Budapest (Academic Journal of Internal Affairs, 2020)
The Compromise of 1867 marked the beginning of a peaceful, prosperous era for Hungary. Due to the increased industrial production and the embourgeoisement, more and more cities in the country became regional centres. Especially the development of Budapest was impressive, which made the capital to a real metropolis in the heart of the Carpathian-Basin by the turn of the century. Its huge factories attracted workers even from long distances, while the newly built market halls and well-known markets provided a reliable source of income for farmers and hawkers of the surrounding settlements. That time, the establishment of a proper railway network and railway connections, gave the basis for the economic prosperity of the country. Thus, in response to “migration” of people, the public transport systems also evolved, having as main function mobility. This could ensure an appropriate level of competitiveness for the economy, a good quality of life and a strong cohesion for the society. Development had not just positive, but also negative sides, such as the appearance of the criminals who harmed the passengers and threatened the safety of rail transport. Nowadays the MAV-Group Zrt is the biggest and most important railway public transport service provider in Hungary. The MAV-START Zrt, a subsidiary exclusively owned by MÁV ZRt, is responsible for the passenger transportation. Today, the MAV-START Zrt handles around 148 million passengers on a yearly basis. However, in the past years increased the number of attacks against the conductors of the trains needing police actions. Our study consists of three main parts. The first part includes a short introduction of the national railway system and the MAV-START Zrt, the second part focuses on the suburban railways, and the third part describes the offences against conductors and their impacts on safety and security regulations of the suburban railways in the urban agglomerations of Budapest.
Keywords: offences; safety and security; railways; train